1995
DOI: 10.1507/endocrj.42.107
|View full text |Cite
|
Sign up to set email alerts
|

Autophosphorylation of Insulin Receptor in a Patient with Werner's Syndrome Associated with Insulin Resistant Diabetes Mellitus.

Abstract: The tissue sensitivity to insulin was evaluated using the hyperinsulinemic euglycemic clamp technique in a 44-year old male with Werner's syndrome associated with diabetes mellitus. In addition, the autophosphorylation of insulin receptors and the number of autophosphorylated insulin receptors were measured in his erythrocytes by a new enzyme-linked immunosorbent assay. He had an increased serum insulin level (30.5 microU/ml) in addition to hyperglycemia (226 mg/dl), suggesting that he had insulin-resistant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In the present study, patients with WS and diabetes had considerable insulin resistance, which may have been associated with insulin receptor abnormalities as the underlying mechanism [15]. It is not clear which organ is responsible for insulin resistance in patients with WS.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the present study, patients with WS and diabetes had considerable insulin resistance, which may have been associated with insulin receptor abnormalities as the underlying mechanism [15]. It is not clear which organ is responsible for insulin resistance in patients with WS.…”
Section: Discussionmentioning
confidence: 57%
“…It is not clear which organ is responsible for insulin resistance in patients with WS. The available reports using a euglycemic hyperinsulinemic clamp with a tracer infusion in patients with WS are limited; however, it has been reported that skeletal muscle demonstrates high insulin resistance on clamp tests [15,16]. In our case, the low Matsuda index reflected the patient's skeletal muscle insulin resistance.…”
Section: Discussionmentioning
confidence: 64%